1967
DOI: 10.1161/01.res.20.5.496
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Canine Atrial Flutter

Abstract: In anesthetized dogs, electrograms were recorded simultaneously from six atrial epicardial sites and a limb or esophageal lead in order to study the mechanism of atrial flutter induced electrically after an intercaval crush in comparison with atrial tachysystole induced by aeonitine. In the former, with limb lead records resembling classical human flutter in form and regularity, activation occupied most of the atrial cycle and progressed in sequence caudally in the right atrium and cranially in the left (count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In fact, as previously summarized, 14 all reliable models of atrial flutter have had to alter the underlying atrial substrate, either by administering exogenous substrates 15,16 or by creating selected lesions. [17][18][19][20][21] Nevertheless, Lewis et al 13 mapped a few selected sites during induced atrial flutter in 4 canine atria and showed that the reentrant circuit traveled either up (inferior to superior) or down (superior to inferior) the right atrial free wall. The remainder of the reentrant circuit was assumed to include left atrial activation and activation around one or both of the great veins (superior and inferior vena cavae).…”
Section: Role Of the Line Of Functional Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as previously summarized, 14 all reliable models of atrial flutter have had to alter the underlying atrial substrate, either by administering exogenous substrates 15,16 or by creating selected lesions. [17][18][19][20][21] Nevertheless, Lewis et al 13 mapped a few selected sites during induced atrial flutter in 4 canine atria and showed that the reentrant circuit traveled either up (inferior to superior) or down (superior to inferior) the right atrial free wall. The remainder of the reentrant circuit was assumed to include left atrial activation and activation around one or both of the great veins (superior and inferior vena cavae).…”
Section: Role Of the Line Of Functional Blockmentioning
confidence: 99%
“…Five subsequent limited mapping studies 15,18 -21 in which either a crush lesion or an incisional lesion was made between the cavae also permitted reliable induction of atrial flutter, again suggesting the importance of a line of block between the cavae to achieve stable atrial flutter. Of note, in one of these studies, 18 incomplete intercaval block in 1 dog resulted in failure of atrial flutter induction.…”
Section: Role Of the Line Of Functional Blockmentioning
confidence: 99%
“…29 "T he internodal pathways form closed loops between the sinoatrial (SA) and atrioventricular (AV) nodes; as preferential pathways, they could play a role in the genesis and maintenance of atrial flutter.' 9 To test this hypothesis, we have examined the possibility of producing circus movement flutter by applying rapidly repetitive stimuli to the left atrium, on the assumption that the junction of Bachmann's bundle with the anterior internodal pathway would provide an asymmetric input into the right atrial internodal complex. We have also studied the effects of increasing the plasma potassium concentration on established flutter.…”
mentioning
confidence: 99%
“…The second step extended the incision caudally to the tricuspid valve and completely transected the ring of atrial tissue around the tricuspid orifice. The reentrant impulse stopped abruptly when it reached the incision, as shown in figure 5. The tachycardia stopped and could not be reinduced after this incision was made.…”
Section: Resultsmentioning
confidence: 96%